Pengaruh Metode Pengolahan Terhadap Total Antosianin dan Uji Aktivitas Antioksidan Pada Jagung Ungu (Zea mays L. var. ceratina Kuleshov) - Putriautami, Fernanda Meyra; Nur, Achamd Vandian; Rahmasari, Khusna Santika; Pambudi, Dwi Bagus (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
Purple corn is a plant belonging to the Poaceae family which has the Latin name Zea mays L. var. ceratina Kuleshov. Purple corn contains anthocyanins which are beneficial for human health as antioxidant agents. Anthocyanins have low stability at high heat and dissolve easily in water. The purpose of this study was to determine the total anthocyanin levels and antioxidant activity of fresh, steamed, and boiled purple corn. This research was conducted qualitatively using thin-layer chromatography with the mobile phase n-Butanol: ethyl acetate: distilled water (4:1:5) and quantitatively using the differential pH method and the antioxidant activity test using the DPPH method. The results obtained from the TLC test showed anthocyanin standard 0.72; fresh purple corn 0.71; steamed purple corn 0.71, and boiled purple corn 0.71. In the qualitative test of total anthocyanin levels using the differential pH method, the total anthocyanins in fresh purple corn were 235,45 mg/100 g; steamed purple corn of 38,908 mg/100 g, and boiled purple corn of 20,42 mg /100 g. From the antioxidant test with the DPPH method, it was obtained that the best IC50 value in fresh purple corn samples of 33.92 (very strong); steamed purple corn was 124.33 (medium) and boiled purple corn was 126.26 (medium).